The Labour Government, 1974-79 - Holmes, Martin. author. aut Link
VII, 213 p.
Keywords: '...in this clear and informed history of the 1974-79 government, Holmes shows how Labour's aspirations constantly encountered the practical limits of economic management.' Times Higher Education Supplement '...lucid and well-documented account.' British Book News '...Dr Holmes is perceptive and fair in his assessment of the leading personalities.' Samuel Brittan, Financial Times.